Validity and reliability of the session RPE method for monitoring exercise training intensity - Herman, L; Foster, C; Maher, MA; Mikat, RP; Porcari, JP (South African Journal of Sports Medicine, 2006)
Objective. The Session Rating of Perceived Extertion (RPE) is a method of measuring exercise intensity that may be useful for the quantitative assessment of exercise training programmes. However, there are inadequate data regarding the validity and reliability of the Session RPE method. This study was designed to evaluate both the validity and reliability of the Session RPE method in comparison to objective measures (%HRpeak, %HRreserve and %VO2peak) of exercise intensity. Methods. Fourteen healthy volunteers (7 male, 7 female) performed 6 randomly ordered 30-minute constant-load exercise bouts at 3 different intensities, with each intensity being repeated. Oxygen consumption (VO2) and heart rate (HR) were measured throughout each exercise bout and normalised to maximal values obtained during a preliminary maximal exercise test. Thirty minutes following the conclusion of each exercise bout, the subject rated the global intensity of the bout using a modification of the Category Ratio (CR) (0 - 10) RPE scale. This rating was compared to the mean value of objectively measured exercise intensity across the duration of the bout. Results. There were significant non-linear relationships between Session RPE and %VO2peak (R2 = 0.76), %HRpeak (R2 = 0.74) and %HRreserve (R2 = 0.71). There were no significant differences between test and retest values of %VO2peak, %HRpeak, %HRreserve and Session RPE during the easy (47 v. 47%, 65 v. 66%, 47 v. 48% and 2.0 v. 1.9), moderate (69 v. 70%, 83 v. 84%, 74 v. 75%, and 4.2 v. 4.3) and hard (81 v. 81%, 94 v. 94%, 91 v. 91% and 7.3 v. 7.4) exercise bouts. Correlations between repeated bouts for %VO2peak (r = 0.98), %HRpeak (r = 0.98), %HRreserve (r = 0.98) and Session RPE (r = 0.88) were significant and strong. Conclusions. The results support the validity and reliability of the Session RPE method of monitoring exercise intensity, although as might be predicted for a subjective method the Session RPE was less precise than the objective measures of exercise training intensity. South African Journal of Sports Medicine Vol. 18 (1) 2006: pp. 14-17